2011
DOI: 10.1105/tpc.111.085852
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Autonomous Promotion of Palisade Cell Development by Phototropin 2 inArabidopsis 

Abstract: Light is an important environmental information source that plants use to modify their growth and development. Palisade parenchyma cells in leaves develop cylindrical shapes in response to blue light; however, the photosensory mechanism for this response has not been elucidated. In this study, we analyzed the palisade cell response in phototropin-deficient mutants. First, we found that two different light-sensing mechanisms contributed to the response in different proportions depending on the light intensity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 58 publications
(145 reference statements)
3
79
0
Order By: Relevance
“…Phototropin (phot) 3 is a BL sensor and was determined to be a receptor for the phototropic response (4). Afterward, phot was shown to mediate chloroplast relocation (5), stomata opening (6), leaf flattering (7), and leaf photomorphogenesis (8). All of these responses serve to optimize the efficiency of photosynthetic activities.…”
mentioning
confidence: 99%
“…Phototropin (phot) 3 is a BL sensor and was determined to be a receptor for the phototropic response (4). Afterward, phot was shown to mediate chloroplast relocation (5), stomata opening (6), leaf flattering (7), and leaf photomorphogenesis (8). All of these responses serve to optimize the efficiency of photosynthetic activities.…”
mentioning
confidence: 99%
“…Physiological analyses with Arabidopsis mutants lacking phot1 and phot2 have revealed that, in addition to regulating the hypocotyl curvature of seedlings toward BL (Huala et al, 1997;Christie et al, 1998), phototropins also regulate a diverse range of responses in flowering plants (Christie and Murphy, 2013;Hohm et al, 2013). These responses include chloroplast movements , nuclear positioning (Iwabuchi et al, 2007), stomatal opening (Kinoshita et al, 2001), sun tracking (Inoue et al, 2008b), leaf expansion (Ohgishi et al, 2004), leaf movements (Inoue et al, 2005), leaf photomorphogenesis (Kozuka et al, 2011), leaf flattening (Sakamoto and Briggs, 2002), and the rapid inhibition of the growth of etiolated hypocotyls (Folta and Spalding, 2001).…”
mentioning
confidence: 99%
“…These include phototropic responses, chloroplast movement, stomatal opening, leaf flattening, and palisade cell development (Huala et al, 1997;Jarillo et al, 2001;Kagawa et al, 2001;Kinoshita et al, 2001;Sakai et al, 2001;Kozuka et al, 2011). With regard to chloroplast movement, phot1 and phot2 redundantly mediate the accumulation response, whereas phot2 alone mediates the avoidance response in Arabidopsis (Jarillo et al, 2001;Kagawa et al, 2001;Sakai et al, 2001).…”
Section: Introductionmentioning
confidence: 99%